DIBALIK LAYAR KAMPANYE: MENGURAI STRATEGI PUBLISITAS DAN PROPAGANDA POLITIK DALAM PEMILIHAN PRESIDEN - Mariam Fatima Barata; Melvin Bonardo Simanjuntak (Jurnal Media dan Komunikasi (MEKAS), 2023)
This study investigates political publicity and propaganda strategies used in presidential election campaigns. The main focus of the study is to reveal behind-the-scenes aspects of political campaigns and analyze the communication strategies used to influence public views and the outcome of presidential elections. In this study, we took the example of the presidential election campaign with a case study on Jokowi's candidate pair - KH. Ma'ruf Amin in the Indonesian presidential election. We used methods of content analysis and interviews with political and communication practitioners to parse the various elements of political publicity and propaganda used during the campaign. The results of this study reveal various communication strategies, messages, narratives, as well as publicity tools used in the campaign. In addition, the study also analyzed the impact of the strategy on public views and presidential election outcomes. The study's findings provide deep insight into the role of political publicity and propaganda in the context of presidential elections, as well as how these strategies influence voter behavior and election outcomes. The implications of this research can help political stakeholders in designing more effective campaign strategies in modern political communication.